Robust image watermarking based on IWT-DCT-SVD for copyright protection - Shubuh, Syafiqul; Ernawan, Ferda; Amrullah, Agit; Wahyu Adi, Prajanto (College of Education, Al-Iraqia University, 2024)
The rapid advancement of technology has resulted in many intellectual works, in the form of images requiring copyright protection to prevent unauthorized use by irresponsible parties. This research examines the hybrid watermarking method that utilises IWT-DCT-SVD domain to enhance the durability of the embedded watermark. The host image is used as the input for the R-Level process, if the watermark logo is small, then the cover image is computed by 3-level of IWT. Whereas, the watermark logo has a large size, the cover image is then computed by 1-level of IWT. The watermark logo is embedded into the singular value of IWT-DCT-SVD for copyright protection. The proposed technique is further assessed and verified by using various attack types. The test findings indicate that the proposed watermarking technology exhibits excellent invisibility and robustness performance, surpassing prior studies. The proposed scheme achieved a high SSIM value of 0.99943, good robustness for NC value from various attacks. These methods are anticipated to provide an alternative answer to watermarking techniques for enhancing the robustness of embedded digital watermarks.